Comparative Analysis of the Role of e-Governance in Rural Development and the Involvement of Rural Populations in its Implementation: A Study of Sonipat and Jind - Gurjeet,; Dr. Bharat Gore, (International Journal of Scientific Research in Humanities and Social Sciences, 2025)
E-governance has emerged as a critical tool for promoting rural development by enhancing access to government services, fostering transparency, and reducing corruption in rural India. This study focuses on the role of e-governance in the districts of Sonipat and Jind in Haryana, evaluating the involvement of rural populations in its implementation. A survey of 400 respondents from these two districts reveals significant insights into the accessibility, awareness, and usage of e-governance services. The findings show that while both Sonipat and Jind have made strides in adopting e-governance, challenges such as unreliable internet infrastructure, digital illiteracy, and limited access to technology remain prevalent. A total of 67.5% of respondents from both districts reported that e-governance services were accessible or very accessible, yet 32.5% still encountered barriers to full usage. Internet infrastructure was perceived to be better in Sonipat, with 36.25% of respondents rating it somewhat better, compared to Jind, where only 20% felt the infrastructure was adequate. The study also highlights a disparity in the level of awareness between the districts, with Sonipat residents reporting slightly higher awareness of e-governance services (38.75% higher awareness) compared to Jind (42.5% reporting equal awareness). Statistical tests, including t-tests, show significant differences in the effectiveness of e-governance in promoting rural development and the involvement of rural citizens in its execution, with Sonipat being perceived to have better service implementation. These findings underscore the importance of improving digital infrastructure, enhancing digital literacy, and increasing awareness to bridge the digital divide and ensure more equitable access to e-governance services.
Keywords: E-Governance; Rural Development; Digital Literacy; Corruption; Transparency; Internet Infrastructure